2018
DOI: 10.1007/s00259-018-3940-4
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid MR-PET of brain tumours using amino acid PET and chemical exchange saturation transfer MRI

Abstract: For the first time, CEST images were compared with F-FET in a simultaneous MR-PET measurement. Imaging findings derived fromF-FET PET and APT CEST MRI seem to provide different biological information. The validation of these imaging findings by histological confirmation is necessary, ideally using stereotactic biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 66 publications
0
10
1
Order By: Relevance
“…Our findings contradict a recent report by da Silva et al [18], who reported no overlap between APTw MRI and FET-PET in simultaneous PET-MRI of eight patients. APTw values cannot be directly compared, because different RF saturation (B 1,rms = 1.0μT, T sat = 0.1 s) and image acquisition techniques (steady-state saturation transfer with 3D gradient echo EPI readout) were used in that study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings contradict a recent report by da Silva et al [18], who reported no overlap between APTw MRI and FET-PET in simultaneous PET-MRI of eight patients. APTw values cannot be directly compared, because different RF saturation (B 1,rms = 1.0μT, T sat = 0.1 s) and image acquisition techniques (steady-state saturation transfer with 3D gradient echo EPI readout) were used in that study.…”
Section: Discussioncontrasting
confidence: 99%
“…In gliomas, a recent study surprisingly reported no correlation between APTw and FET [18]. Given the partially overlapping biological processes captured by these imaging modalities, these findings motivated us to investigate the synergism of APTw, FET, and CBV and how well they capture cellularity and vascularisation in a series of patients with newly diagnosed gliomas, both in IDH mutant and wild type tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Although amino acid PET and advanced MRI such as perfusion-weighted imaging or chemical exchange saturation transfer are increasingly gaining attention in Neuro-Oncology (Langen et al, 2017; da Silva et al, 2018), to date conventional MRI is the method of choice in brain tumor diagnostics. Several studies have investigated the potential of conventional MRI for differentiation of radiation injury from brain metastasis recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies evaluated CEST in patients with GBM [75,76,77], only few studies directly compared amino acid PET and CEST in more than 5 patients. Da Silva et al [78] compared FET PET and APT CEST MRI in 8 high-grade gliomas patients using a 3 T hybrid PET/MR scanner. The authors showed that FET PET and APT CEST are spatially incongruent and reflect different biological information.…”
Section: Amino Acid Pet and Cestmentioning
confidence: 99%